Peran Ibu-Ibu TP-PKK Desa Senggigi sebagai Agen Perubahan melalui Program Urban Farming Terintegrasi - Dewi, Suprayanti Martia; Maryanti, Sri; Cicilia, Sisca; Kisman, Kisman; Sukmana, Febrian Humaidi; Putri, Dwi Noorma; Apriani, Reni (Universitas Mataram, 2025)
This community service activity was carried out in Senggigi Village, West Lombok Regency, with the aim of increasing the capacity and social role of Senggigi residents, especially the TP-PKK women of Senggigi Village, as agents of change through the implementation of urban farming based on an Integrated Farming System (IFS). The activities included socialization, training in horticultural cultivation (eggplant, chili, tomato, water spinach, pakcoy), poultry raising, catfish farming through budikdamber and independent ponds. The activities were accompanied by intensive mentoring throughout the program. During the mentoring process, significant social transformation was observed, reflected in increased motivation, commitment, and solidarity among members, alongside the development of technical cultivation skills; as well as the initiative of TP-PKK women in implementing urban farming activities to improve family food security. The tangible products produced by the partners included eggs, homegrown vegetables, and catfish harvested during the program. This program provides a tangible and effective impact in strengthening family food security while also creating beneficial group activities, particularly in managing home gardens based on an integrated agricultural system in Senggigi Village.